Spray pyrolysis of CuBi2O4 photocathodes: improved solution chemistry for highly homogeneous thin films. Issue 25 (5th June 2017) - Wang, Fuxian; Chemseddine, Abdelkrim; Abdi, Fatwa F.; van de Krol, Roel; Berglund, Sean P.
Abstract : Dense, homogeneous CuBi2 O4 thin films are prepared, for the first time, by spray pyrolysis. Abstract : Dense, homogeneous CuBi2 O4 thin films are prepared, for the first time, by spray pyrolysis. Major challenges related to the chemical stability of the precursor solution and spreading behavior of the sprayed droplets are revealed and addressed. Triethyl orthoformate (TEOF) is added as a water scavenger to avoid fast hydrolysis and polycondensation of bismuth ions in the precursor solution, thereby reducing powder formation during the spray deposition process. Polyethylene glycol (PEG) is used to improve the spreading behavior of sprayed droplets over the entire CuBi2 O4 film surface, which prevents powder formation completely and allows for the deposition of dense, homogeneous films with thicknesses over 420 nm. These highly uniform CuBi2 O4 thin films are well-suited for fundamental studies on the optical and photoelectrochemical properties. Additionally, they produce record photocurrent densities for CuBi2 O4 up to 2.0 mA cm −2 under AM1.5 simulated sunlight along with incident photon-to-current efficiency (IPCE) and absorbed photon-to-current efficiency (APCE) values up to 14% and 23%, respectively (for 550 nm light at 0.6 VRHE with H2 O2 as an electron scavenger).